Ethnobotany of the Use of Nelambo Suon (Bikkia sp.) Plants Based on the Traditional Knowledge of the Yali Tribe, Papua Pegunungan Province - Tomi A. Nelambo; Suharno Suharno; Omes Momiake; Oviana Mohi (Jurnal Biologi Papua, 2025)
The use of plants for human needs is very high, especially among communities in suburban and rural areas. Communities are highly dependent on forests as their main source of sustenance. The purpose of this study was to determine the use of Nelambo Suon (Bikkia sp.) plant stems among the Yali tribe in Yahukimo Regency, Papua. The method used was a survey, which was conducted through field observations and interviews using questionnaires. This study was conducted in four villages, namely Sabelebi, Muhumu, Kinkun, and Ohena, in the Heriapini District of Yahukimo Regency, Papua Mountains. This study involved 43 respondents consisting of primary informants, key informants, and supplementary informants. The results of the study show that the Bikkia plant is widely used by the Yali tribe in the Papua Mountains. The bark can be used as a remedy for malaria, while the trunk is used to make sehen arrows, suap arrows, and wangkun sticks (for harvesting crops). As many as 88.37% of the community acknowledged that the trunk of this tree is very strong and can be used for various purposes. However, conservation efforts for this plant have not yet been undertaken by the community. Considering that Bikkia sp., found in Yahukimo, is one of several species with limited distribution in the world, conservation efforts are needed.